DETERMINATION OF SETTLING EFFICIENCY AND OPTIMUM PLATE ANGLE FOR PLATED SETTLING TANKS - DEMIR, A (PERGAMON-ELSEVIER SCIENCE LTD, 1995)
In this work, the experimental results obtained under different surface loadings and plate angles in parallel plate settling tanks were statistically evaluated. A general equation about settling efficiency was expressed by applying two-stage nonlinear regression. The results, which had been calculated by using this general equation, were compared with experimental values and the plate angle providing maximum settling efficiency was determined.
Keywords: SEDIMENTATION TANKS; LAMELLA SETTLING TANKS; Engineering; Environmental Sciences & Ecology; Water Resources